PELAKSANAAN PROGRAM KEMITRAAN PT. TELEKOMUNIKASI INDONESIA WITEL RIAU DARATAN, TBK DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR - Andria, Mhd Zahroni; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Implementation of the Partnership Program PT. Telekomunikasi Indonesia Witel Riau Daratan, Tbk very helpful for the government in realizing equitable welfare economic development for all Indonesian people. The implementation of the partnership program is based on the Republic of Indonesia Minister of State Regulation Number: PER-09 / MBU / 07 of 2015 about partnership program and community developmen of state- owned enterprises.. However, even though it has been regulated by the regulation there are still failures in the implementation of partnership program. Research conducted using qualitative methods. this study uses the theoretical concept of the prinsip elements of the partnership by Julius Bobo (2003), namely: Cooperation, Betwen Large and Medium Entrepreneurs with Small Entrepreneur Need, Mutual Reinforcement and Mutual Benefit. Data collection techniques in this study were carried out observation, interviews, documentation and literature study using descriptive techniques. The results of the study explained that the implementation of the PT. Telekomunikasi Indonesian Witel Riau Daratan, Tbk has not implemented a good partnership pettern. So that the implementation is not effective and efficient. Factors that hinder the implementation of the partnership program by PT. Telekomunikasi Indonesian Witel Riau Daratan, Tbk in Koto Mesjid Sub District XIII Koto Kampar namely: Failed to Establish Communication, Lack of Openness. Less Strict Sanctions.Keywords : Implementation, Partnership Program, PT. Telekomunikasi Indonesian Witel Riau Daratan, Tbk.